Уламжлалт мэдлэгийн холбогдолтой үг, хэллэгийн судалгаа (Малын зарим тоног, хэрэгслийн нэрийн жишээгээр): The Research of Knowledge Related to Traditional Vocabulary and Terminology - E., Altanshagai (Mongolian Journal of Foreign Languages and Cultures, 2023)
This article shows the statistical results of sociolinguistic research on practical knowledge of traditional vocabulary and terminology associated with nomadic livestock industry accessories. The study was conducted among two groups of high schoolers of the 11th-grade general education school of Ulaanbaatar, and the 11th-grade general education school of the Bayandelger sum of Sukhbaatar aimag. It is noted that the number and age of participants /15-16 years old/ of the survey, respectively, is identical. Comparative results of the research, data on the practical knowledge of the survey participants in the field of traditional vocabulary and terminology related to livestock industry accessories are attached in percentage terms. The study showed that participants’ practical knowledge of traditional terminology of livestock equipment varied by species. In recent few decades, due to urbanization, the current social situation and the needs arising from it, the migration of people to urban areas has continuously increased, which ultimately led to the way of life of the Mongols intensively moving away from the traditional way of life of a nomadic civilization based on animal husbandry. At the same time, the results of the study show that the rapid development of technology, the consumer world of electronic and digital gadgets and social networks actively influence the interests of children and youth, create new conditions in the trend of modern education, the demand for jobs and professions. As a result, these social factors have a significant impact on the acquisition of traditional knowledge among the younger generation.